1981
DOI: 10.1002/aja.1001620302
|View full text |Cite
|
Sign up to set email alerts
|

Circadian organization of thirteen liver and six brain enzymes of the mouse

Abstract: The activities of 13 liver and 6 brain enzymes were studied in 7-12 week old CD2F1 male mice that had been fed ad libitum and standardized either to 12 hours of light (0600-1800) alternating with 12 hours of darkness (1800-0600) (LD12:12); or to a reversed light-dark cycle (darkness 0600-1800; light 1800-0600) (DL12:12). Three separate studies were performed on two different days; in each experiment, subgroups of 14 animals were sacrificed at 3-hour intervals. Livers were assayed for: isocitrate dehydrogenase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 20 publications
4
14
0
Order By: Relevance
“…Particularly, LDH 1 is in myocardium, in red blood cells, in kidney (at cortical level) and in skeletal muscles; LDH 2 is in myocardium, in red blood cells, in kidney (at cortical level), in pancreas, in lung and in skeletal muscle LDH 3 is in lung, placenta, in skeletal muscle and in pancreas; LDH 4 in kidney (at medulla level), in skeletal muscles, in lung and in placenta; LDH 5 is in liver, kidney (at medulla level), skeletal muscle and in pancreas (Wolf and Williams, 1973). In previous studies (North et al, 1981;Zaleska-Freljian and Priebe, 1991) LDH showed rhythmicity with acrophases prior to the dark onset that seemed to be influenced by feeding (Sitren and Stevenson, 1978). In our study, liver LDH showed a rhythmic pattern coincident with values reported in literature (Figures 2A and B).…”
Section: Discussionsupporting
confidence: 91%
“…Particularly, LDH 1 is in myocardium, in red blood cells, in kidney (at cortical level) and in skeletal muscles; LDH 2 is in myocardium, in red blood cells, in kidney (at cortical level), in pancreas, in lung and in skeletal muscle LDH 3 is in lung, placenta, in skeletal muscle and in pancreas; LDH 4 in kidney (at medulla level), in skeletal muscles, in lung and in placenta; LDH 5 is in liver, kidney (at medulla level), skeletal muscle and in pancreas (Wolf and Williams, 1973). In previous studies (North et al, 1981;Zaleska-Freljian and Priebe, 1991) LDH showed rhythmicity with acrophases prior to the dark onset that seemed to be influenced by feeding (Sitren and Stevenson, 1978). In our study, liver LDH showed a rhythmic pattern coincident with values reported in literature (Figures 2A and B).…”
Section: Discussionsupporting
confidence: 91%
“…Most enzymes from young mice had acrophases which were within the last half of the light and the first half of the dark span. This result was similar to other work where acrophases tended to be at the time of transi tion from light to dark [North et al, 1981]. The acrophases of enzymes from old mice were similar to those of young mice, except in the case of LDH, and no new pattern con cerning response to the SLD schedule was observed.…”
Section: Resultssupporting
confidence: 79%
“…The SLD system may have been a confounding factor. In a previous study [North et al, 1981], where young mice were standardized for 2 weeks to a single light-dark schedule (LD), the rhythms observed in these enzymes were de scribed well by a cosine function. In the cur rent study, most of these enzymes did not fit the cosine function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18) Because there are significant circadian rhythms in enzyme activity, 19,20) renal function, 21,22) blood flow, 23) and protein binding, 24) the pharmacokinetics and pharmacodynamics of many drugs are affected by circadian variations. 25,26) DPD, a major catabolic enzyme of 5-FU, has been reported to exhibit a circadian rhythm, and the variations have been correlated with the efficacy and toxicity of 5-FU in experimental animals 6,7) and cancer patients.…”
Section: Discussionmentioning
confidence: 99%